Diagnostic Performance of Diffusion-weighted Imaging for Evaluation of Bowel Inflammation in Paediatric Inflammatory Bowel Disease: A Systematic Review and Meta-analysis. (22nd June 2021) - Kim, Pyeong Hwa; Yoon, Hee Mang; Jung, Ah Young; Lee, Jin Seong; Cho, Young Ah
Abstract: Background and Aims: The diagnostic performance of diffusion-weighted imaging magnetic resonance enterography [DWI-MRE] has not been clearly established in a paediatric population. We systematically evaluated the diagnostic performance of DWI-MRE for the detection of bowel inflammation in paediatric patients with suspected or known inflammatory bowel disease [IBD]. Methods: MEDLINE/PubMed, EMBASE, Web of science and the Cochrane library were searched for articles investigating the diagnostic performance of DWI-MRE for the detection of bowel inflammation in paediatric patients with suspected or known IBD up to December 31, 2020. Pooled sensitivity and specificity were calculated using a bivariate random-effects model. Pooled inter-reader agreement for the interpretation of DWI-MRE was also calculated. This study was registered as PROSPERO CRD42021228754. Results: Nine studies covering 400 paediatric patients were included. The pooled sensitivity and specificity of DWI-MRE for the detection of bowel inflammation were 0.93 (95% confidence interval [CI], 0.88–0.96) and 0.96 [95% CI, 0.87–0.99], respectively. Substantial heterogeneity was noted in both sensitivity [ I 2 = 66%; p < 0.01] and specificity [ I 2 = 94%; p < 0.01]. Meta-regression analysis identified that the use of spasmolytics contributed to higher specificity [0.89–0.99] and that quantitative assessment with an apparent diffusion coefficient cut-off value contributed to lower sensitivity [0.93–0.85] and specificity [0.98–0.72]. The pooled coefficient of inter-reader agreement, including four studies using visual assessment, was 0.97 [95% CI, 0.78–1.00]. Conclusions: DWI-MRE, especially when used with spasmolytics, is accurate for the detection of bowel inflammation in paediatric patients with suspected or known IBD. Quantitative measurement of ADC is not practical for this purpose.